The Influence of Peer Education on SADARI (Self-Breast Examination) Behaviour in Preventing Breast Cancer for Woman of Childbearing Age in South Lampung, Indonesia - Dewi Yuliana; Radella Hervidea (Journal for Quality in Public Health, 2020)
Breast cancer is a malignant tumor which developed in breast cells. According to WHO, an effective method to improve earlier breast cancer detection is by self-breast examination and this is proven to reduce breast cancer mortality rate since 1990. The objective of this research was to find out the influence of peer education on SADARI (self-breast examination) behaviour in preventing breast cancer for woman of childbearing age in South Lampung, Indonesia. This was a quantitative study by using pre-experimental approach and one group pretest and posttest design. The samples were 32 respondents who were taken by using random sampling. Data were obtained through questionnaires and analyzed by using statistic test with t-dependent test (paired t-test). The result shows that there is an influence of peer education on SADARI behaviour in preventing breast cancer for woman of childbearing age in South Lampung, Indonesia with p-value 0.000. SADARI behavior can be done to women as a self-examination, especially women of childbearing age to prevent breast cancer.